Dalit Theology and Indian Christian History in Dialogue: Constructive and Practical Possibilities - Andrew Ronnevik (Religions, 2021)
In this article, I consider how an integration of Dalit theology and Indian Christian history could help Dalit theologians in their efforts to connect more deeply with the lived realities of today’s Dalit Christians. Drawing from the foundational work of such scholars as James Massey and John C. B. Webster, I argue for and begin a deeper and more comprehensive Dalit reading and theological analysis of the history of Christianity and mission in India. My explorations—touching on India’s Thomas/Syrian, Catholic, Protestant, and Pentecostal traditions—reveal the persistence and complexity of caste oppression throughout Christian history in India, and they simultaneously draw attention to over-looked, empowering, and liberative resources that are bound to Dalit Christians lives, both past and present. More broadly, I suggest that historians and theologians in a variety of contexts—not just in India—can benefit from blurring the lines between their disciplines.